Electron Bottleneck in the Charge/Discharge Mechanism of Lithium Titanates for Batteries. Issue 10 (17th April 2015) - Ventosa, Edgar; Skoumal, Marcel; Vazquez, Francisco Javier; Flox, Cristina; Arbiol, Jordi; Morante, Joan Ramon
Abstract: The semi‐solid flow battery (SSFB) is a promising storage energy technology featured by employing semi‐solid fluid electrodes containing conductive additive and active Li‐ion battery materials. The state of art anode material for SSFB is Li4 Ti5 O12 (LTO). This work shows that LTO improves drastically the performance in fluid electrode via hydrogen annealing manifesting the importance of the electrical conductivity of the active material in SSFBs. On the other hand, the properties of fluid electrodes allow the contributions of ionic and electrical resistance to be separated in operando. The asymmetric overpotential observed in Li4 Ti5 O12 and TiO2 is proposed to originate from the so‐called electron bottleneck mechanism based on the transformation from electrically insulator to conductor upon (de‐)lithiation, or vice versa, which should be considered when modelling, evaluating or designing advanced materials based on Li4 Ti5 O12, TiO2 or others with insulating‐conducting behavior materials. Abstract : Remember the titanates: The contributions of ionic and electrical resistances during charge/discharge are difficult to separate in solid electrodes, while the latter largely dominates in fluid electrodes. An electron bottleneck mechanism originating from the transformation of active materials from electrically insulating to conducting upon (de)lithiation explains the highly asymmetric overpotentials observed in fluid electrodes.